Global Nonexistence for a Viscoelastic Wave Equation with Boundary Dissipative - Quispe Méndez, Teófanes (2016)
We consider a mixed problem for a viscoelastic nonilinear wave equation with boundary dissipative lineal and nonlinear source term. We prove the existence and uniqueness of its local solution by the Faedo-Galerkin method and show the blow-up of solutions by the energy method.